From Grey to Green: Transforming Informal Financial Practices Towards Sustainable Funding - Alfina Rahmatia; Arief Dwi Saputra (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
Informal financial practices, also known as grey finance, have always contributed to the economies of many countries, especially in communities with limited or no access to formal financing facilities. This study aims to address the transformation of these informal financial practices into sustainable financing mechanisms that align with the current global trend for green and ethical financial models. Sentiment and discourse analysis were used to understand the perceptions, motivations, and challenges from a financial transition perspective. The information is extracted from various empirical data in the form of interviews and textual data from previous research articles. Data analysis is conducted using Nvivo 12 software. Sentiment analysis helps identify the emotional tone of sentiments that describe the process of societal transformation. Discourse analysis is conducted in-depth to find the role tendencies in previous research. Among the discursive themes are trust, financial inclusion, environmental responsibility, and regulatory challenges significant in establishing a path toward sustainable finance. This study helps understand how informal financial practices can be restructured in line with ethical and sustainable financial principles while generating essential insights for policymakers and financial practitioners working at the intersection of grey and green finance. Ultimately, the study calls for an inclusive financial system sensitive to socio-economic and environmental variables. It promises to create a resilient and sustainable global financial system.